De bacharel a professor: a construção dos saberes pedagógicos na educação profissional - Santos, Thalita Alves (2016)
This work is part of the area of concentration: Educational Institution and Educator Training specifically on the Research Line of Training and Teaching the Teacher Professional Practice, Masters Program in Education of the University Universidade do Oeste Paulista (Unoeste) in Presidente Prudente - São Paulo. The study proposed here aimed to investigate how the construction of pedagogical knowledge by teachers of vocational education IFSP Campus President Epitácio is held. This is an interpretative descriptive, of phenomenological orientation, characterized as a case study, carried out at the Federal Institute of Education, Science and Technology of São Paulo - Campus President Epitácio. It was realized a data collection from the application of the interviews that allowed inferring the professional / educational profile of these teachers and investigate his career; it was held the observation of classes, aiming to highlight the teaching practice. It was also performed the analysis of documents, building the amalgam of the existing theoretical base, with recent research dealing with relevant issues to this study, along with laws, decrees and edicts regulating this type of education. This stage permeated the development of the preceding ones. The collected material was interpreted from the adopted theoretical framework and it was also used the content analysis for this purpose, as categories of analysis there are: the professional profile, the educational profile, the construction of pedagogical knowledge and the management of matter. As a result, we have: pedagogical knowledge characterize the specific knowledge of the professional practice of teaching; They are built by our participants in practice, based on the trial / error; the need for teacher training for action in education is marked by features such as emergency, special and provisional; that its importance is not recognized either by the institution or by teachers themselves; that the practices of these teachers have gaps that deserve reflections for a more effective teaching, and the understanding that the vast majority of participants have on teaching and learning is superficial.